The Voices of Macao Stones - Ride, Lindsay, Sir, 1898-1977 (Book collections on Project MUSE., 1999)
The stones, statues and memorials found all over Macao trace the story from the days of the first Portuguese navigators to reach China in the sixteenth century to the events of more recent times.